Organizational identity work in MNE subsidiaries: Managing dual embeddedness - Colman, Helene Loe; Grøgaard, Birgitte; Stensaker, Inger G. (Journal of International Business Studies, 2022)
This paper adopts an organizational identity work perspective to examine how MNE subsidiaries manage dual embeddedness to strategically position themselves in both their local context and in the global MNE. Prior research suggests that although dual embeddedness provides benefits, it also brings challenges, as subsidiaries must effectively balance external pressures and expectations with internal ones. Through a qualitative case study of organizational identity work in the subsidiaries of a Norwegian MNE, we reveal the process through which subsidiary members manage dual embeddedness in their day-to-day work. We develop a model that conceptualizes organizational identity work in MNE subsidiaries as an ongoing process, one that enables the subsidiary to position itself as a legitimate actor across contexts, while reproducing the perceived tensions of dual embeddedness. This combination thus continually fuels organizational identity work. Our findings have both theoretical and managerial implications. We provide important theoretical insight into how MNE subsidiaries achieve flexibility to position themselves as globally and locally embedded. For managers, this implies that trying to remove the tensions of dual embeddedness – for instance, by privileging the global above the local – may hinder flexibility.